IMPLEMENTATION, CHALLENGES AND SOLUTIONS OF MULTICULTURAL EDUCATION IN SCHOOL - Tira Nur Fitria (English Language Education Department, Faculty of Teacher Training and Education, Syekh-Yusuf Islamic University (PBI FKIP UNIS), 2023)
This research describes the implementation, challenges, and solutions of multicultural education. This research is library research. The analysis shows that multicultural education promotes equality in schools to develop students' attitudes toward diversity and living together in harmony. Multicultural education is a reform movement aimed at providing equal opportunities for all students, regardless of their ethnicity, culture, language, religion, race, or class. It is crucial in Indonesia, where the school system is a social system with individuals from different backgrounds united. The success of multicultural education depends on the desire and care of the school community, especially teachers. Teachers must innovate to teach multicultural education, aiming to increase student motivation and tolerance towards diversity. In a multicultural classroom, all students from different cultures and languages have equal educational opportunities. Learning reflects culture, experiences, perspectives on linguistics and culture of a group, as well as respect for differences and student cultural similarities. Having a positive attitude towards differences can bring individuals into the community and bring the community into the wider world community. However, challenges during the implementation of multicultural education may. Indonesia's education policy should promote a democratic, egalitarian society that respects the values of humanity and equality, and values differences.